Sistem Pakar Diagnosa Kerusakan Laptop Menggunakan Metode Forward Chaining - Suminten Suminten; Rani Rani (Jurnal RESTI (Rekayasa Sistem dan Teknologi Informasi), 2018)
Expert system is an aplication that can perform activities. This system can make a diagnosis like humans, foe example diagnosing hardware and software damage on laptops. This system is widely used in the field of science. This system contains the knowledge of the experts which transferred into the aplications. This system is mode to find a solution as an experts. Expert system can also provide an explanation of steps taken, and provide advice or conclusions on the type or damage to the laptop. This system is developed with purpose to help the users, from hadware and software damage. The case of damageneeden an expert in the settlement with her or his (expert) knowledge already transferred into the application. This system using forward chaining search method. This reasoning is used to examine the factors that are incorperated by rules stored in system, so that it can be concluded from factors collected. The software used to build that is dreamweaver, and to process the database using apache. The evaluation of system performance is using quesioner which elistributed to 100 respondents. The functionality criteria, a total is 861 and average is 86,1. The efficiency 843 and average is 84,1. The uasbility 824 and an average is 82,4 and then total portability is 810 with an average is 81,0.